Formation of triple-helical structures by the 3′-end sequences of MALAT1 and MENβ noncoding RNAs - Brown, Jessica A. (National Academy of Sciences, 2012)
Stability of the long noncoding-polyadenylated nuclear (PAN) RNA from Kaposi's sarcoma-associated herpesvirus is conferred by an expression and nuclear retention element (ENE). The ENE protects PAN RNA from a rapid deadenylation-dependent decay pathway via formation of a triple helix between the U-rich internal loop of the ENE and the 3′-poly(A) tail. Because viruses borrow molecular mechanisms from their hosts, we searched highly abundant human long-noncoding RNAs and identified putative ENE-like structures in metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) and multiple endocrine neoplasia-β (MENβ) RNAs. Unlike the PAN ENE, the U-rich internal loops of both predicted cellular ENEs are interrupted by G and C nucleotides and reside upstream of genomically encoded A-rich tracts. We confirmed the ability of MALAT1 and MENβ sequences containing the predicted ENE and A-rich tract to increase the levels of an intronless β-globin reporter RNA. UV thermal denaturation profiles at different pH values support formation of a triple-helical structure composed of multiple U•A-U base triples and a single C•G-C base triple. Additional analyses of the MALAT1 ENE revealed that robust stabilization activity requires an intact triple helix, strong stems at the duplex-triplex junctions, a G-C base pair flanking the triplex to mediate potential A-minor interactions, and the 3′-terminal A of the A-rich tract to form a blunt-ended triplex lacking unpaired nucleotides at the duplex-triplex junction. These examples of triple-helical, ENE-like structures in cellular noncoding RNAs, are unique.